Vertical conveyor driving the integration of moisture transported by the westerlies to the Asian water towers’ atmospheric water cycle - Jing Gao; Tandong Yao; Valérie Masson-Delmotte; Martin Werner; Jean Jouzel; Lonnie Thompson; Mathieu Casado; Hans Christian Steen-Larsen; Alexandre Cauquoin; Ellen Mosley-Thompson; Zeqing He; Rong Cai; et al. (Proceedings of the National Academy of Sciences, 2026)
The westerlies moisture transport underpins water security for over two billion people dependent on the Asian water towers (AWTs). However, the mechanisms by which large-scale westerlies-advected moisture is integrated into the AWTs’ atmospheric water budget remain poorly understood due to observational gaps. Here, we combine three-dimensional observations of atmospheric water vapor stable isotopes with isotope-enabled modeling. We identify the conveyor mechanism that regulates the vertical moisture transport under calm conditions during the winter-spring period when the westerlies are dominant. Sharp vertical isotopic gradients show that large-scale westerlies-advected moisture is predominantly confined aloft, while local residual moisture persists near the surface. Our results show the interplay of the westerlies’ subsidence at night with thermodynamically distinct local residual air, yielding thermal inversions and condensation that suppresses vertical mixing and decouples moisture between the free troposphere and the atmospheric boundary layer. This process constitutes a primary pathway for integrating westerlies-advected moisture into the local moisture budget without precipitation, sustaining near-surface moisture accumulation. Our results provide critical benchmarks for improving atmospheric models, refining climate projections of the intensifying water cycle over the AWTs, and advancing interpretations of isotopic records in regional climatic archives.